Asuhan Keperawatan Pada Tn. A dengan Gangguan Sistem Imunologi: (Febris Akut di Ruang Dahlia Rsud Dr. Soeselo Kabupaten Tegal) - Putri Dwi Kamala; Tati Karyawati; Ahmad Zakiudin (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Febrile illnesses can be caused by a wide variety of viruses, bacteria, and other pathogenic microbes, and their production originates from outside the body. These substances, known as exogenous pyrogens, can enter the human system through contaminated water, food, or direct human-to-human transmission. Once inside the body, exogenous pyrogens stimulate the immune system by triggering the release of endogenous pyrogens such as cytokines, which in turn act on the hypothalamus to increase body temperature as a defense mechanism. This physiological response, while protective, can also indicate an underlying infection that may need prompt medical treatment. According to the World Health Organization (WHO) in 2020, the number of fever cases worldwide reached approximately 11–20 million people annually, with an estimated 128,000–161,000 deaths each year due to complications from febrile illnesses (Meirita et al., 2024). The global burden of fever varies by region; for example, in the United States, South America, and Western Europe, the incidence of fever is estimated to reach 4–5% of the population. In contrast, several Asian countries report higher prevalence rates, such as Japan with 6–9%, India with 5–10%, and Guam with 14% (Ulum et al., 2024). These statistics highlight the ongoing public health challenge posed by febrile illnesses, emphasizing the need for improved surveillance, prevention strategies, and treatment protocols worldwide.